2001
DOI: 10.1007/bf03012136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resting brain conditions measured by two different methods (i.v. and oral administration) with18F-FDG-PET

Abstract: Our aim was to evaluate regional differences between brain activity in two resting control conditions measured by 3D PET after administration of FDG through either the intravenous (i.v.) or the oral route. Ten healthy male volunteers engaged in the study as the i.v. group (mean age, 26 +/- 9.3 years, +/- S.D.) who received FDG intravenously and another 10 volunteers as the oral group (mean age, 27.9 +/- 11.3 years, +/- S.D.) who received FDG per os. A set of 3D-PET scans (emission and transmission scans) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Pain or stress may have effects on 18 F-FDG biodistribution that could be confounding. Masud et al showed quantitative differences in brain glucose metabolism between the oral and intravenous routes of 18 F-FDG administration (12). They observed glucose metabolism to be significantly higher in the superior frontal gyrus, superior parietal lobule, lingual gyrus, and left cerebellar hemisphere in the intravenous group than in the oral group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain or stress may have effects on 18 F-FDG biodistribution that could be confounding. Masud et al showed quantitative differences in brain glucose metabolism between the oral and intravenous routes of 18 F-FDG administration (12). They observed glucose metabolism to be significantly higher in the superior frontal gyrus, superior parietal lobule, lingual gyrus, and left cerebellar hemisphere in the intravenous group than in the oral group.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested performing radiation dosimetry studies, especially for gut and liver, before use in humans. Masud et al compared brain images obtained after intravenous and oral 18 F-FDG administration in healthy humans (12). The blood activity curve build-up phase after oral administration was slow and continued until around 110-120 min.…”
mentioning
confidence: 99%